TERJEMAH AL-QURAN BAHASA JAWA BANYUMASAN: EPISTEMOLOGI DAN KONTRIBUSINYA DALAM MELESTARIKAN BAHASA LOKAL - Istianah, Istianah; Eman Surya, Mintaraga (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2020)
This study aims to analyze the epistemology of "Al-Quran and the Banyumasan Javanese Translation" (hereinafter abbreviated as QTJB) compiled by 10 translators with different scientific backgrounds. This research is qualitative research which aims to: 1) determine the background of the compilation of "Al-Quran and the Javanese Banyumasan Translation" and a description of the social space when the translation is compiled; 2) knowing the source and method of translation; and 3) knowing the contribution of the translation of the Al-Quran in the Javanese Banyumas language in preserving local languages, especially the Javanese Banyumas language. This study found that the QTJB manuscript uses the ḥarfiyyah translation method as well as the ṭafsīriyyah method armed with the Koran and its translation (QTK) published by the Ministry of Religion as the main reference and several classical commentaries and the Banyumas-Indonesian dialect dictionary. The results of translating the Koran into the Javanese Banyumasan language in the form of the QTJB manuscripts did not add new vocabulary to the Banyumas Javanese vocabulary, but QTJB took another form in the preservation of the Banyumas Javanese language by reintroducing vocabulary. forgotten words and almost wiped out from the vocabulary of today's society.